Enhanced V-Model - Durmus, Mustafa Seckin; Ustoglu, ilker; Tsarev, Roman Yu.; Börcsök, Josef (Informatica, 2018)
Typically, software development processes are time consuming, expensive, and rigorous, particularly for safety-critical applications. Even if guidelines and recommendations are defined by sector-specific functional safety standards, development process may not be completed because of excessive costs or insufficient planning. The V-model is one of the most well-known software development lifecycle model. In this study, the V-model lifecycle is modified by adding an intermediate step. The proposed modification is realized by checking the fault diagnosability of each module. The proposed modification provides three advantages: (1) it checks whether the constructed model covers all software requirements related with faults; (2) it decreases costs by early detection of modeling deficiencies before the coding and testing phases; and (3) it enables code simplicity in decision of fault occurrence.